Beyond the “Indigenizing the Academy” Trend: Learning from Indigenous Higher Education Land-Based and Intercultural Pedagogies to Build Trans-Systemic Education - Drouin-Gagné, Marie-Eve (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
Given the UNDRIP’s assertion of Indigenous Peoples’ rights to their education and knowledge systems, and in the wake of the Truth and Reconciliation Commission of Canada’s calls to action, many Canadian Universities are considering “Indigenizing the Academy.” Yet, the meaning of such undertaking remains to be clarified. This article explores trans-systemic approaches as a possible avenue for “Indigenizing the Academy,” and, more specifically, what Indigenous higher education programs and institutions can contribute to a trans-systemic approach to education. Considering two existing models I encountered in my doctoral research, namely the Intercultural approach as developed in the Andes (García et al., 2004; Mato, 2009; Sarango, 2009; Walsh, 2012), and land-based pedagogy as developed in North America (Coulthard, 2017; Coulthard & Simpson, 2016; Tuck et al., 2014; Wildcat et al., 2014), I argue they present trans-systemic elements that would allow us to re-think the frameworks in which to engage with Indigenous Peoples’ rights and knowledge systems in the mainstream academy. What could be learned from the principles and practices of these two Indigenous higher education philosophies to articulate Indigenous knowledge into trans-systemic education in the mainstream academy in ways that foster solidarity and mutual understanding between Indigenous and non-Indigenous people?